Deepening Class Insight Through Participatory Lesson Study: An Experience with Students Specializing in School Psychology - Pasmanik-Volochinsky, D; Jorquera-Martinez, C (John Wiley and Sons Inc, 2024)
Class phenomena have primary significance for the diagnosis and intervention at both an individual and a whole-class level for school psychologists. Trying to bring undergraduate psychology students closer to class and teaching, a learning experience based on an adaptation of Lesson Study, a professional development method for teachers, was designed and evaluated with a group of undergraduate psychology students attending two preparatory and consecutive courses for professional performance in educational environments. Students made participants observations of classes they attended, participated in collaborative reflection with their teachers, and issued a report. Meetings were transcribed, conforming, altogether with their written reports 12 texts, analyzed using thematic analysis. Four primary themes were generated concerning benefits, difficulties, perceived learning facilitators and this experience s contribution to professionalization. The results stress a favorable self-perceived effect in students comprehension of the class and the teaching, backed up by an internship experience. Additionally, content expressing empathy toward teachers and an increased perceived self-knowledge as students was reported. Having a previous experience with the method within the first course and a part time internship in the second course, along with the profile of the second course and its emphasis on procedural content, seemed to foster these outcomes. © 2024 Wiley Periodicals LLC.